Analisis pengaruh citra perusahaan terhadap loyalitas nasabah: Studi kasus asuransi jiwa bersama Bumiputera 1912 - Izzaini, Muhammad Fadhil (Maliki Interdisciplinary Journal, 2024)
Insurance companies are companies that protect in the field of financing and risk transfer, risks can occur without any signs or occur suddenly, so there must be preparation to deal with these unexpected risks. Bumi Putera Joint Life Insurance Company is one of the pioneer and oldest insurance companies in Indonesia, as one of the oldest insurance companies, of course there are many problems that have been faced by this company, especially the issue of misappropriation of funds by the AJB Bumiputera Company, this is due to an error in human resource management, the selection of human resources who are less competent and expert is one of the root problems which then becomes a big problem for the company. The number of problems in the company’s body causes a loss of customer trust, and this affects the company’s image which is an important aspect for all companies, so research is carried out regarding the effect of company image on customer loyalty and the results of the company’s image greatly affect customer loyalty, a good company image will attract loyal customers and attract other customers.